USING THE NEW DEFINITION OF HYPERTENSION FROM THE 2017 U.S. GUIDELINE FOR HIGH BLOOD PRESSURE (BP) IN ADULTS: CHANGES IN CONTROL OF HYPERTENSION IN A SAMPLE OF OUTPATIENT CLINICS. (June 2018) - Egan, B.; Wozniak, G.; Yang, J.; Davis, R.; Sutherland, S.; Rakotz, M.
Abstract : Objective: The 2017 AHA/ACC Hypertension Guideline (HGL) lowers the threshold for defining hypertension (HTN) to BP > 130/80 mmHg and sets treatment targets for most to < 130/80 mmHg. We examined the impact of these changes on control rates compared to JNC-7. Design and method: 16 Family Medicine clinics in South Carolina, U.S. participated in a six month hypertension quality improvement program in 2017. BP data from patients with at least one visit during the intervention period (16, 344) were analyzed to compare changes in BP control using JNC-7 criteria (BP control < 140/90 mmHg) to those in the new HGL (BP < 130/80 mmHg). Results: Applying the new HGL more than doubles prevalent uncontrolled hypertension, from 5, 534 to 11, 191 patients. These additional 5, 657 adults with a visit during the intervention period would be reclassified as uncontrolled, and HTN control prevalence would decline more than one-half from 65.6% to 30.8%. Among specific sub-groups, control rates decreased from 65.4% to 35.0% for patients greater than or equal to 65 years of age, from 68.4% to 31.8% for white patients, and from 59.4% to 23.7% for African Americans. Conclusions: The impact of the new HGL compared with JNC-7 reduces control rates more than 50% in our sample. Variation exists among sub-groups, with the largest decrease in BP control of 60% occurring in African Americans.